Localisation and characterisation of dystrophin in the central nervous system of controls and patients with Duchenne muscular dystrophy. Issue 4 (April 1994) - Uchino, M; Teramoto, H; Naoe, H; Yoshioka, K; Miike, T; Ando, M
Abstract : The aim was to localise and characterise dystrophin in various human tissues, especially in the CNS. Immunoblotting and immunostaining studies were carried out with eight region-specific dystrophin antibodies. In necropsy tissue from controls, dystrophin was noted as a doublet in immunoblots of striated muscle, and as a single band in those of smooth muscle and the CNS. With immunostaining, punctate immunoreactivity was seen on the cell bodies and dendrites of the cerebral cortical neurons and cerebellar Purkinje cells. By contrast, dystrophin was not detected in any tissues, including the cerebrum and cerebellum, of patients with Duchenne muscular dystrophy who had an intellectual disturbance.